Examining predictors of initial outpatient psychiatric treatment for conduct problems in youth: A records review. Issue 2 (4th April 2017) - Watson, Gabriel C.; Carlson, John S.; Magen, Jed
Abstract: Purpose: To investigate predictors of conduct problem (CP) treatment in an outpatient child psychiatry clinic. Design and Methods: Medical records ( N = 78) of youth with CPs (71% male; mean age = 9.9 years) were analyzed to determine how treatment history, race, gender, travel distance, aggression symptoms, internalizing disorder symptoms, and age of diagnosis influenced initial treatment decisions. Findings: Severity of aggression symptoms and travel distance significantly increased the likelihood that initial treatments included psychotropic medication. Travel distance also moderated the relationship between history of psychosocial intervention for CPs and treatment recommendations. Practice Implications: Adhering to treatment guidelines for youth with CPs is essential for furthering evidence‐based psychiatric nursing care.